Challenges for Successful Planning of Open and Distance Learning (ODL): A Template Analysis - Minnaar, Ansie (International Review of Research in Open and Distributed Learning, 2013)
How to plan an open and distance learning (ODL) unit in higher education is not clearly described in the literature. A number of ODL facilities at residential universities have not been successful because of a lack of planning or because of failure to ensure that all the different systems for ODL delivery were in place and functioning. This paper sheds light on how to plan strategically and how to implement an ODL unit at an existing university. A template analysis was used to construct a road map for ODL planners. We used this analytical tool to organise data from a large collection of articles, books, and documents from 1980-2010. We purposefully chose template analysis as a document analysis process to foster the recurring themes found in published articles on planning and implementing ODL facilities in higher education. The results indicate four main strategies for successful implementation of an ODL unit. The template consists of strategic planning, policies, systems, and challenges. It was concluded that the template for ODL planning offers new insight into distance education. It could be used as a foundation for ODL planning, implementation, monitoring, and evaluation. We recommend further research on the template with the aim of theory construction for ODL planning and implementation.